Acceptability of constraint induced movement therapy: influence of perceived difficulty and expected treatment outcome. Issue 7 (3rd October 2022) - Andrabi, Mudasir; Taub, Edward; Mckay Bishop, Staci; Morris, David; Uswatte, Gitendra
ABSTRACT: Background: Constraint-Induced Movement (CI) Therapy has evidence of efficaciously rehabilitating upper-extremity hemiparesis after stroke. Yet, it is not widely used in the United States. One barrier appears to be the perception of its difficulty among stroke care consumers, as reported by two published studies in which the participants had little or no apparent direct exposure to CI Therapy. Objectives: Assess the perception of difficulty of CI Therapy by individuals with chronic stroke who have actually undergone CI Therapy. Methods: A secondary analysis was conducted of data from two randomized controlled trials of CI Therapy. Participants had chronic, mild-to-moderate upper-extremity hemiparesis after stroke. The Motor Activity Log and Wolf Motor Function Test were used to measure motor function of the more-affected arm. A Patient Opinion Survey assessed participants' perception of difficulty and satisfaction with treatment. Results: The participants (N = 40) showed large improvements in motor function of their more-affected arm after treatment, p's <001. CI Therapy was perceived to be of only moderate difficulty by participants before treatment (mean = 4.4 out of 7). Perception of its difficulty decreased afterward (mean = 3.7, p = .002). Moreover, participants were highly satisfied with their outcomes (mean = 6.3 out of 7). Satisfaction was positively related to the improvements in more-affected arm use in everyday life, Δ R 2 = .3, p < .001. Conclusions: Chronic stroke survivors who have actually had CI Therapy perceive it to be of only moderate difficulty and are highly satisfied. Negative views about its acceptability warrant reconsideration.